Emerging infectious diseases: Epidemiological perspective - Shuvankar Mukherjee (Wolters Kluwer Medknow Publications, 2017)
Over the past 30 years, at least 30 new infectious diseases have emerged to threaten the health of millions of people across the globe. The major challenge to combat these infections is that for many of them, there is no specific treatment or cure or vaccine. There is limited scope of preventing or controlling them. The contributory factors include urbanization and destruction of natural habitats, climate change and changing ecosystems, changes in population of reservoir hosts or intermediate insect vectors and microbial genetic mutation, international trade and commerce, change in human demographics and behavior, lack of public health services and infrastructure, and antibiotic resistance. It is clear by now that the problem of emerging infectious disease (EID) is not restricted to any single country, and a strong and sustainable international collaboration will be needed in their prevention and control. India along with other countries in the South-East Asian region will continue to bear the brunt of the burden of EIDs in years to come.